Demand for financial information in small business management: Empirical study - Jacek Jaworski (e-Finanse: Financial Internet Quarterly, 2012)
Limited access of small enterprises to reliable and well-prepared information about their condition is mentioned as one of the main barriers to small business development. One of the key types of information used in management is financial information. It concerns the resources and financial flows in the enterprise. The main goal of the paper is to present the results of the questionnaire survey conducted in mid. 2010 among managers of small enterprises in Poland. The survey was used to recognize the usefulness of financial information in decision-making, to diagnose information needs of entrepreneurs and to identify factors affecting these needs.
Keywords: M19; M21; M49; 330; small business management; information in decision making; manager's information needs; KMU; Mittelstandsmanagement; Wirtschaftsinformation; Entscheidung; Polen